Necator americanus infection: a possible cause of altered dendritic cell differentiation and eosinophil profile in chronically infected individuals. - Ricardo T Fujiwara; Guilherme G L Cançado; Paula A Freitas; Helton C Santiago; Cristiano Lara Massara; Omar Dos Santos Carvalho; Rodrigo Corrêa-Oliveira; Stefan M Geiger; Jeffrey Bethony (PLoS Neglected Tropical Diseases)
Background Hookworms survive for several years (5 to 7 years) in the host lumen, inducing a robust but largely ineffective immune response. Among the most striking aspects of the immune response to hookworm (as with many other helminths) is the ablation of parasite-specific T cell proliferative response (hyporesponsiveness). While the role of the adaptive immune response in human helminth infection has been well investigated, the role of the innate immune responses (e.g., dendritic cells and eosinophils) has received less attention and remains to be clearly elucidated. Methodology/principal findings We report on the differentiation/maturation of host dendritic cells in vitro and the eosinophil activation/function associated with human hookworm infection. Mature DCs (mDCs) from Necator americanus (Necator)-infected individuals showed an impaired differentiation process compared to the mDCs of non-infected individuals, as evidenced by the differential expression of CD11c and CD14. These same hookworm-infected individuals also presented significantly down-regulated expression of CD86, CD1a, HLA-ABC, and HLA-DR. The lower expression of co-stimulatory and antigen presentation molecules by hookworm-infected-derived mDCs was further evidenced by their reduced ability to induce cell proliferation. We also showed that this alternative DC differentiation is partially induced by excreted-secreted hookworm products. Conversely, eosinophils from the same individuals showed a highly activated status, with an upregulation of major cell surface markers. Antigen-pulsed eosinophils from N. americanus-infected individuals induced significant cell proliferation of autologous PBMCs, when compared to non-infected individuals. Conclusion Chronic N. americanus infection alters the host's innate immune response, resulting in a possible modulation of the maturation process of DCs, a functional change that may diminish their ability for antigen presentation and thus contribute to the ablation of the parasite-specific T cell proliferative response. Interestingly, a concomitant upregulation of the major cell surface markers of eosinophils was observed in hookworm-infected individuals, indicative of antigen-specific immune responses, especially antigen presentation. We showed that in addition to the postulated role of the eosinophils as effector cells against helminth infection, activated cells may also be recruited to sites of inflammation and contribute to the immune response acting as antigen presenting cells.